Can investment activities in the form of capital formation influence economic growth in South Africa? - Ncanywa, T.; Makhenyane, L. (SAAPAM (South African Association of Public Administration and Management), 2016)
The study examined the impact of investment activities as measured by gross fixed capital formation (GFCF) on economic growth of South Africa for the period from 1960 to 2014. The Johansen co-integration and the vector error correction model (VECM) were used to examine the impact. Results revealed that gross fixed capital formation has a positive relationship with economic growth both in the short and the long run. There is also bidirectional causality between the gross capital formation and economic growth. It is recommended that investment activities can be a tool both in the long and short run to boost the economy, and ultimately improve the citizen's livelihood.
Article
Keywords: Gross fixed capital formation; Investment activities; Economic development -- South Africa; Investments; Saving and investment